The discriminant validity of a standardized testing battery and its ability to differentiate anthropometric and physical characteristics between youth, academy, and senior professional rugby league players - Dobbin, N.; Highton, J.; Moss, S. L.; Twist, C. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To assess whether a standardized testing battery can differentiate anthropometric and physical qualities between youth, academy, and senior rugby league players and determine the discriminant validity of the battery. Methods: A total of 729 rugby league players from multiple clubs in England categorized as youth (n = 235), academy (n = 362), and senior (n = 132) players completed a standardized testing battery that included the assessment of anthropometric and physical characteristics during preseason. Data were analyzed using magnitude-based inferences and discriminant analysis. Results: Academy players were most likely taller and heavier than youth players (effect size [ES] = 0.64-1.21), with possibly to most likely superior countermovement jump, medicine-ball throw, and prone Yo-Yo Intermittent Recovery Test Level 1 (Yo-Yo IR1) performance (ES = 0.23-1.00). Senior players were likely to most likely taller and heavier (ES = 0.32-1.84), with possibly to most likely superior 10- and 20-m sprint times, countermovement jump, change of direction, medicine-ball throw, and prone Yo-Yo IR1 than youth and academy players (ES = -0.60 to 2.06). The magnitude of difference appeared to be influenced by playing position. For the most part, the battery possessed discriminant validity with an accuracy of 72.2%. Conclusion: The standardized testing battery differentiates anthropometric and physical qualities of youth, academy, and senior players as a group and, in most instances, within positional groups. Furthermore, the battery is able to discriminate between playing standards with good accuracy and might be included in future assessments and rugby league talent identification.